SATB2 is frequently expressed in ossifying and non-ossifying peripheral oral fibroma of the gingival region but not in reactive fibromatous lesions from other intraoral sites - Baněčková, Martina; Agaimy, Abbas (Annals of Diagnostic Pathology, 2020)
Ossifying and non-ossifying peripheral oral fibromas (POF) of the gingival and alveolar mucosa are localized, cellular, small fibrous nodular lesions likely resulting from diverse external/ internal physical and chemical irritation or injuries. A central nidus of metaplastic woven bone characterizes and defines the ossifying variant. The inherent tendency of these lesions to ossify remains elusive. We herein analyze SATB2 expression as osteoblastic transcription and differentiation factor in 28 gingival POFs (10 of them ossifying) and compare them to 28 fibrous lesions from different non-gingival intraoral sites. Strong to moderate diffuse nuclear SATB2 immunoreactivity was detected in all ossifying (10/10; 100%) and in 8/18 (44%) non-ossifying gingival POFs, but in only 1/28 (3%) non-gingival oral reactive nodular fibrous lesions. This study illustrates for the first-time consistent expression of the osteoblastic marker SATB2 in ossifying and most of non-ossifying POFs of the gingival area but lack of this marker in reactive fibrous lesions from other oral cavity sites. This finding is in line with the proposed origin of gingival POFs from periodontal ligaments and may explain the frequent ossification observed in them. It is mandatory to consider this finding when assessing biopsies from SATB2-positive oral cavity neoplasms to avoid misinterpretation.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Fibrous epulis; Jaw tumors; Non-ossifying fibroma; Oral cavity; Ossifying fibroma; Peripheral oral fibroma; SATB2